Coalescence and compensatory elongation due to the effect of internal and external sandhi in Aymara, an aspect to be taken into account in the written standard - Huayhua Pari, Felipe (2014)
In the written language, we can lead ourselves by certain norms because of the typology of the language, as the phonological and morphophonemic processes, while in oral language, it is not necessary because it is implicit. When the writers get in the aimara coding, they have to respect the rules called sandhi. That is why we bring it up some aspects to be taken into account for writing prectices.